2017
DOI: 10.1007/s00153-017-0544-9
|View full text |Cite
|
Sign up to set email alerts
|

On constructions with 2-cardinals

Abstract: We propose developing the theory of consequences of morasses relevant in mathematical applications in the language alternative to the usual one, replacing commonly used structures by families of sets originating with Velleman's neat simplified morasses called 2-cardinals. The theory of related trees, gaps, colorings of pairs and forcing notions is reformulated and sketched from a unifying point of view with the focus on the applicability to constructions of mathematical structures like Boolean algebras, Banach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In [34] and [32] one may find more open problems. Two other papers on topics related to this paper which we have not mentioned are [17] and [15]. In the former, Laver shows, among other things, why one cannot approach the question of Hajnal and Szentmiklóssy in the usual way as in the Baire space, which is to say, by iteratively adding functions dominating modulo finite.…”
Section: Introductionmentioning
confidence: 95%
“…In [34] and [32] one may find more open problems. Two other papers on topics related to this paper which we have not mentioned are [17] and [15]. In the former, Laver shows, among other things, why one cannot approach the question of Hajnal and Szentmiklóssy in the usual way as in the Baire space, which is to say, by iteratively adding functions dominating modulo finite.…”
Section: Introductionmentioning
confidence: 95%
“…where for two sets A, B of ordinals A < B means that α < β for any α ∈ A and β ∈ B. For more details on the structure of µ see [19…”
Section: Preliminariesmentioning
confidence: 99%
“…and α ∈ Y = Y 1 * Y 2 and the ranks of X 1 , X 2 , Y 1 , Y 2 are elements of µ of fixed rank n ∈ N. By [19, Definition 1.1(3)] there is an order preserving f Y,X : X → Y , which by [19, Definition 1.1 (3,5)] must satisfy f [X 1 ] = Y 1 and f [X 2 ] = Y 2 and moreover f (X ∩ (α + 1)) is the identity on X ∩ (α + 1) be the coherence lemma 2.1 of [19], so f Y,X (α) = α and f [X…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Koszmider (see [Kos17,Proposition 4.3] or [Kos95, Proposition 10]) has shown that if µ is a (κ, λ)-semimorass then it satisfies the following non-reflection property: for every proper subset X λ with |X| ≥ κ we have µ ∩ P κ X ∈ NS κ,X .…”
Section: Introductionmentioning
confidence: 99%